Instruction-based selective action pattern (IBSAP): a novel method for talent identification in sports - Sagdilek, E.; Sahin, S. K. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Background and Study Aim: Talent identification/development programs are utilized by sports federations to select or train elite athletes. In addition to the established tests that assess perceptive and motor skills, it was deemed significant that cognitive skills should be evaluated as well. The present study was undertaken to assess the utility of Instruction-Based Selective Action Pattern (IBSAP), a novel method that we developed, in estimating perceptive, motor as well as cognitive skills of athletes in order for talent identification. We also investigated the relationship between IBSAP and auditory reaction times (ARTs). Material and Methods: Forty-three students (average age: 12.6 years) participated in the study. Random/fixed-interval ARTs were recorded. IBSAP was applied using a table tennis robot that was set up to throw 30 balls in three different colors to different spots on the table with a frequency of 1 ball/s. The subjects were instructed to ignore the white balls, to touch the yellow balls, and to catch the pink balls before the first trial and their scores were calculated in two consecutive trials according to a scoring system. Results: Our results showed that motor learning, adaptation and reinforcement of the participants were significantly greater in second trial compared with the first trial and that IBSAP values were correlated with ARTs. Conclusions: We conclude that the IBSAP method reliably provides quantitative data on perception, motor as well as cognitive skills and it can be considered as a useful tool for talent identification.